Analisis Decision Tree dan Random Forest untuk Perubahan Penggunaan Lahan Terbangun - Dhia Zalfa Zahira; Dinna Maulia; Elysabeth Nindy Nasing (Jurnal Riset Perencanaan Wilayah dan Kota, 2026)
Abstract. The expansion of built-up areas is a critical issue in the spatial and environmental dynamics of Bekasi City and Regency, a rapidly growing industrial and residential area. This study examines the monitoring and analysis of land cover change, specifically how the choice of classification algorithms Decision Tree and Random Forest interacts with sampling strategy in handling imbalanced class conditions, and identifies the most influential spatial factors. This study uses Sentinel-2 Land Cover data from 2017 and 2020, along with spatial predictor variables, namely proximity to roads, tollways, water bodies, economic centres, stations, industrial areas, and population density. Models were developed using three sampling strategies (proportional, stratified, and balanced) with hyperparameter tuning. Results indicate that RF outperformed DT, achieving an Overall Accuracy of 0.81 and a Kappa coefficient of 0.62 under the balanced sampling scenario with an 80:20 training-to-testing split. Feature importance analysis shows that proximity to toll gates and roads was the dominant factor, followed by economic centres and stations. In this study, RF was more effective than DT in handling imbalanced data and produced more stable results. These findings can support spatial planning and land-use control based on spatial data and machine learning. Abstrak. Perluasan kawasan terbangun menjadi isu utama dalam dinamika tata ruang dan lingkungan di Kota dan Kabupaten Bekasi yang berkembang pesat sebagai kawasan industri dan permukiman. Penelitian ini mengkaji mengenai pemantauan dan analisis perubahan lahan, khususnya terkait bagaimana pemilihan algoritma klasifikasi Decision Tree dan Random Forest berinteraksi dengan strategi sampling dalam menangani kondisi data yang tidak seimbang (imbalanced class), serta mengidentifikasi faktor spasial yang paling berpengaruh. Kajian ini menggunakan data Land Cover (Sentinel-2 ) tahun 2017 dan 2020 serta variabel prediktor spasial, yaitu kedekatan dengan jalan, tol, badan air, pusat ekonomi, stasiun, kawasan industri, dan kepadatan penduduk. Model dikembangkan menggunakan tiga strategi sampling (proportional, stratified, dan balanced) disertai tuning hyperparameter. Hasil menunjukkan RF lebih unggul dengan overall accuracy 0,81 dan Kappa 0,62 pada skenario balanced sampling dengan pembagian training dan testing 80:20. Analisis feature importance menunjukkan bahwa kedekatan dengan gerbang tol dan jalan adalah faktor dominan, diikuti pusat ekonomi dan stasiun. Pada kajian ini, RF lebih efektif dibandingkan dengan DT dalam menangani data tidak seimbang serta memberikan hasil yang lebih stabil. Temuan ini dapat mendukung perencanaan tata ruang dan pengendalian alih fungsi lahan berbasis data spasial dan machine learning.